Imprime PGG Enhances Anti-Tumor Effects of Tumor-Targeting, Anti-Angiogenic, and Immune Checkpoint Inhibitor Antibodies - Chan, Anissa S. H.; Kangas, Takashi O.; Qiu, Xiaohong; Uhlik, Mark T.; Fulton, Ross B.; Ottoson, Nadine R.; Gorden, Keith B.; Yokoyama, Yumi; Danielson, Michael E.; Jevne, Trinda M.; Michel, Kyle S.; Graff, Jeremy R.; et al. (Frontiers in Oncology, 2022)
Imprime PGG (Imprime) is in late-stage clinical development as a combinatorial agent with several therapeutic modalities. Here we present pre-clinical mechanistic data supportive of Imprime, a soluble yeast β-1,3/1,6-glucan pathogen-associated molecular pattern able to prime innate immune cells in a Dectin-1 dependent manner. In tumor-free mice, Imprime evoked broad innate immune responses (type I interferon signature, mobilization of myeloid cells, dendritic cell and monocyte/macrophage expression of co-stimulatory ligands like CD86, and activation of natural killer cells). Imprime-mediated activation of myeloid cells also resulted in functional priming of antigen-specific CD8 T cell response. In tumor-bearing mice, Imprime monotherapy further resulted in activation of systemic and tumor infiltrating macrophages and enhanced cytotoxic CD8 T cell trafficking. Imprime enhanced the anti-tumor activity of several combinatorial agents in mouse cancer models; anti-tyrosinase-related protein 1 antibody in B16F10 melanoma experimental lung metastasis model, anti-vascular endothelial growth factor receptor 2 antibody in H1299 and H441 lung cancer, and anti-programmed cell death protein 1 antibody in MC38 colon cancer models. Mechanistically, combining Imprime with these combinatorial therapeutic agents elicited enhanced innate immune activation, supporting immunological synergy. Finally, Imprime treatment induced similar in vitro phenotypic and functional activation of human innate immune cells. Collectively, these data demonstrate Imprime’s potential to orchestrate a broad, yet coordinated, anti-cancer immune response and complement existing cancer immunotherapies.